2017
DOI: 10.1136/bcr-2016-218748
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant-related nephropathy in a patient with IgA nephropathy

Abstract: SUMMARYAnticoagulant-related nephropathy is a type of acute kidney injury caused by overcoagulation. We describe a case of an 84-year-old man with arterial hypertension, coronary heart disease and atrial fibrillation treated with acenocoumarol, who presented with haematoproteinuria and acute kidney injury during a phase of excessive anticoagulation. In addition to IgA nephropathy, renal biopsy also revealed acute tubular necrosis, red blood cell casts and positive iron staining in tubular cells. After this acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Even a moderate increase in INR has been shown to aggravate macroscopic hematuria in patients with IgAN leading to AKI [7]. Recently, it has been shown that ARN is not only observed in patients with warfarin but also in those receiving DOAC [8][9][10][11][12]. In our patient, the coagulopathy could be potentiated by the underlying liver cirrhosis in addition to dabigatran.…”
Section: Discussionmentioning
confidence: 66%
“…Even a moderate increase in INR has been shown to aggravate macroscopic hematuria in patients with IgAN leading to AKI [7]. Recently, it has been shown that ARN is not only observed in patients with warfarin but also in those receiving DOAC [8][9][10][11][12]. In our patient, the coagulopathy could be potentiated by the underlying liver cirrhosis in addition to dabigatran.…”
Section: Discussionmentioning
confidence: 66%
“…So far, the known risk factors for ARN are pre-existing CKD, advanced age, body weight, diabetic nephropathy, arterial hypertension, glomerulonephritis and heart failure (6,10,11). The main preventive measure is the adjustment of anticoagulant dose, particularly in CKD patients.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only 4 cases of ARN in patients with IgA nephropathy have been reported, of which 2 patients were treated with dabigatran, 3 one patient was treated with acenocoumarol, 6 and only one patient was treated with warfarin. 7 IgA nephropathy leads to glomerular hemorrhage and macroscopic hematuria through RBC accumulation within the glomerulus and casts that can occlude the tubules. Subsequent events including interstitial hemorrhage and oxidative stress on the kidney lead to the overall progression of ARN.…”
Section: Discussionmentioning
confidence: 99%